Viabilitas benih dan pertumbuhan bibit kakao (Theobroma cacao L) pada beberapa jenis media simpan dan tingkat kelembaban - Dian Wirawan Tambunsaribu; Syaiful Anwar; Dwi Retno Lukiwati (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2017)
The research aimed to study the effect of type and humidity level of storage media and teir interaction on cacao seed viability and seedling growth. The experiment was arranged in a completely randomized factorial design 3 x 4 with three replications. The first factor is the type of storage media (P) which is control (P0), charcoal shell (P1), and sawdust (P2). The second factor is the humidity content of storage media (K) which is control (K0), moisture content 15% (K1), moisture content 30% (K2), moisture content 45% (K3). Parameters observed were seeds moisture content, electrical conductivity (EC), seed germination, germination vigor, germination rate, height of seedling, leaf number of seedling, dry weight of seedling and hypothetic vigor index of seedling. Data were analyzed by anova and followed Duncan’s Multiple Range Test (DMRT). The treatments of charcoal shell and sawdust gave not significant effect to cacao seed viability and seedling growth, but it’s interactions gives significan effect the observed parameters. Combined use of charcoal shell storage media with humidity content 30% gives the highest result to cacao seed viability and seedling growth after storage.Keywords : seed viability, storage media, humidity level and cacao